1994
DOI: 10.1021/np50104a011
|View full text |Cite
|
Sign up to set email alerts
|

Two New Macrolide Sesquiterpene Pyridine Alkaloids from Maytenus emarginata: Emarginatine G and the Cytotoxic Emarginatine F

Abstract: Two new macrolide sesquiterpene pyridine alkaloids, emarginatine F [1] and emarginatine G [2], were isolated from Maytenus emarginata. The structural determinations of 1 and 2 by 2D nmr techniques and spectral comparison with a related compound, emarginatine A [3], are discussed. Biological evaluation showed that emarginatine F [1] demonstrated strong cytotoxicity against human epidermoid carcinoma of the nasopharynx (KB), ileocecal adenocarcinoma (HCT-8), melanoma (RPMI-7951) and medulloblastoma (TE-671) tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 3 publications
1
40
0
Order By: Relevance
“…HSQC and HMBC data further supported the assignment of the 2,3-disubstituted pyridine unit (Supplemental Table 1). A dicarboxy side chain containing two esters, one methine, two methylenes, one ethyl group, and the 2,3-disubstituted pyridine unit supported the presence of a cassininic acid moiety in oppositine A (1). The NMR data for this portion of the molecule are consistent with data reported for the analogous protons in the compounds cassinine 13 and orthophosphonine.…”
supporting
confidence: 79%
“…HSQC and HMBC data further supported the assignment of the 2,3-disubstituted pyridine unit (Supplemental Table 1). A dicarboxy side chain containing two esters, one methine, two methylenes, one ethyl group, and the 2,3-disubstituted pyridine unit supported the presence of a cassininic acid moiety in oppositine A (1). The NMR data for this portion of the molecule are consistent with data reported for the analogous protons in the compounds cassinine 13 and orthophosphonine.…”
supporting
confidence: 79%
“…Kuo (1994) isolated two sesquiterpenes from M. emarginata namely 'emarginatine F' and . Each data point represents the mean of data from three wells (n = 3).…”
Section: Discussionmentioning
confidence: 99%
“…The authors also have identified cytotoxic sesquiterpene pyridine alkaloids, including emarginatines B (I7) and F (I8), from M. emarginata (Willd.) Ding Hou (90,91). Recently, new triterpenes were isolated from M. chuchuhuasca R. Hamet and Colas (92), along with sesquiterpenes from the same plant (93).…”
Section: Maytenus Speciesmentioning
confidence: 99%